2011
DOI: 10.1055/s-0031-1300359
|View full text |Cite
|
Sign up to set email alerts
|

New Quinoxaline 1,4-Di-N-oxides for Treatment of Tuberculosis

Abstract: Some quinoxaline 1,4-di-N-oxides derivatives with very different substituents in 2, 3, 6 and 7 positions have been synthesized in order to obtain new hypoxia selective agents. Some of these products have been tested as antituberculosis agents and very interesting results have been obtained from the first screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…As a result of the anti-tuberculosis research project, our group published several studies in which the synthesis and biological evaluation of a large amount of quinoxaline and quinoxaline 1,4-di-N-oxide derivatives have been described [5][6][7][8][9][10][11][12][13][14][15]. From these studies, several quinoxaline-2-carboxylate 1,4-N-oxide derivatives, with different patterns of substituents at quinoxaline nucleus, were prepared and they showed important antitubercular activity in vitro, 1-43 ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the anti-tuberculosis research project, our group published several studies in which the synthesis and biological evaluation of a large amount of quinoxaline and quinoxaline 1,4-di-N-oxide derivatives have been described [5][6][7][8][9][10][11][12][13][14][15]. From these studies, several quinoxaline-2-carboxylate 1,4-N-oxide derivatives, with different patterns of substituents at quinoxaline nucleus, were prepared and they showed important antitubercular activity in vitro, 1-43 ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[18] More than thousand available descriptors exist and are reported in the literature, and one has to decide how to select those that characterize the property under consideration in the best possible manner. Although a large number of structure-activity relationships (SARs) were reported previously for analyzing the biological properties displayed by quinoxaline derivatives, none of these included QSAR results [5][6][7][8][9][10][11][12][13][14][15][19][20][21][22]. A main reason of this can be attributed to the fact that in past decades few experimental biological data on quinoxaline compounds were available for building a quantitative model, but nowadays this drawback is continuously being surmounted by different research groups that register new data into the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, our group reported interesting results of 2-quinoxalinecarbonitrile derivatives obtained from the first screening; Carta's team did the same with quinoxaline-2-one derivatives [37]. During these past few years, our group studied the influence of the 1,4-di-N-oxide groups in quinoxaline ring on the antimycobacterial activity, confirming their importance to increase the activity [34][35][36].…”
Section: General Backgroundmentioning
confidence: 84%
“…The first publications regarding quinoxaline derivatives as anti-Mycobacterium agents date back to the end of the 1990s [34][35][36]. Herein, our group reported interesting results of 2-quinoxalinecarbonitrile derivatives obtained from the first screening; Carta's team did the same with quinoxaline-2-one derivatives [37].…”
Section: General Backgroundmentioning
confidence: 89%
“…Some of these organic derivatives have shown excellent M. tuberculosis growth inhibition values. It has been observed that generally the lack of the two N-oxide groups has lead to the loss of the antimycobacterial activity [11][12][13][14]. On the other hand, the relationship between iron, mycobacteria and tuberculosis is well known.…”
Section: Introductionmentioning
confidence: 99%